2019 IEEE Intelligent Vehicles Symposium (IV) 2019
DOI: 10.1109/ivs.2019.8814146
|View full text |Cite
|
Sign up to set email alerts
|

PWOC-3D: Deep Occlusion-Aware End-to-End Scene Flow Estimation

Abstract: In the last few years, convolutional neural networks (CNNs) have demonstrated increasing success at learning many computer vision tasks including dense estimation problems such as optical flow and stereo matching. However, the joint prediction of these tasks, called scene flow, has traditionally been tackled using slow classical methods based on primitive assumptions which fail to generalize. The work presented in this paper overcomes these drawbacks efficiently (in terms of speed and accuracy) by proposing PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 31 publications
(42 reference statements)
0
48
0
Order By: Relevance
“…Specifically, the full search space of such operation is 3D, being it over pixel coordinates plus displacement between correlation curves. We refer the reader to the supplementary material for some examples supporting this rationale, while ablation studies reported among our experiments prove the effectiveness of such a new layer, allowing DWARF to outperform similar architectures (Saxena et al 2019) on the KITTI online benchmark.…”
Section: Cost Volumes and 3d Correlation Layermentioning
confidence: 56%
See 1 more Smart Citation
“…Specifically, the full search space of such operation is 3D, being it over pixel coordinates plus displacement between correlation curves. We refer the reader to the supplementary material for some examples supporting this rationale, while ablation studies reported among our experiments prove the effectiveness of such a new layer, allowing DWARF to outperform similar architectures (Saxena et al 2019) on the KITTI online benchmark.…”
Section: Cost Volumes and 3d Correlation Layermentioning
confidence: 56%
“…Recently, Saxena et al (2019) proposed a fast and lightweight model taking into account occlusions. Although similar in design, we will show that DWARF outperforms it by a good margin.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, the CNN-based scene flow methods have shown the good performance on both computational accuracy and efficiency [57]- [59]. However, most of these CNN-based usually approaches require supervised training process and may have difficulty to be directly applied to real world data where ground truth is not easily accessible.…”
Section: Related Workmentioning
confidence: 99%
“…A rigid plane model performs poorly when applied to deformable objects, and ego-motion estimation for highly dynamic scenes is hard. (Menze and Geiger, 2015) CSF (Lv et al, 2016) Deep Learning Fast Poor generalization PWOC-3D (Saxena et al, 2019) DRISF (Ma et al, 2019) Sparse-to-Dense Comparatively fast, good generalization Sensitive to distribution of matches SFF Schuster et al (2018c) SFF++ (ours)…”
Section: Related Workmentioning
confidence: 99%
“…Methods which are guided by semantic segmentation from deep neural networks will generalize badly to other domains, unless they are fine-tuned for the new task. Same is assumed for upcoming purely learning based approaches (Ma et al, 2019;Saxena et al, 2019) which are potentially even faster than our approach. SFF++ focuses especially on robustness across domains and applications.…”
Section: Related Workmentioning
confidence: 99%